Kearifan Lokal dan Pelestarian Lingkungan (Studi Kasus di Kampung Naga, Kabupaten Tasikmalaya, dan di Kampung Kuta, Kabupaten Ciamis) - Yus Darusman (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2014)
This study aims to find information from the local people about life that is unified with nature, living hormonious with nature, nature management and preservation that take place naturally. It used qualitative method by interviewing participans and snow ball approach. Data was reduced and analyzed from the begining of the study. The attitude of simple traditional society with its local wisdom has proven the existence of a harmonious relation between human importance and nature preservation. It is understandable that behind a simple life pattern possessed by traditional society, there are a lot of significance towards the continuance of human life. Without being aware that the relation between human and natural components (ecosystem) have been embodied. Ecofeminism has been existed in the traditional society, to organize the relation not only between human, but also between human and nature. The attitude of being friendly to environment (ecofeminism) is patterned in the form of suggestion and inhibition when humans are in touch with the nature, such as; someone has to be in a sacred state when enrolling a sacred forest (having ablution), it is not allowed to bring any sharp weapons inside, to pick or cut any kinds of tree, unallowed to hunt animals, etc. ABSTRAKPenelitian ini bertujuan untuk memperoleh informasi dari masyarakat adat tentang kehidupan yang menyatu dengan alam, hidup bersama dengan alam, pengelolaan dan pelestarian alam dapat berlangsung secara tradisional. Penelitian kualitatif dengan menggunakan interviu participant dan pendekatan snow ball, data direduksi dan dianalisis dari awal penelitian. Hasil penelitian menunjukkan, bahwa masyarakat tradisional yang bercorak sederhana dengan sejumlah kearifan lokal yang dimilikinya telah membuktikan adanya hubungan yang serasi dengan alam. Tanpa disadari oleh masyarakat adat, bahwa jalinan hidup antara manusia dengan alam menyatu dalam bentuk perilaku beretika lingkungan; menghargai dan menyadari akan kesatuan hidup antara komponen yang ada di alam, serta saling ketergantungan hidup, antara komponen di alam (ekosistem). Ekofeminisme ternyata sudah ada pada masyarakat adat, tidak hanya mengatur hubungan antara manusia saja, melainkan juga mengatur hubungan dengan alam sekitar. Perilaku ramah lingkungan terpolakan ke dalam anjuran dan larangan dalam berhubungan dengan alam.